Bioactive compounds, antioxidant and antibacterial properties of the pulp, peel and aril of the fruit of Clusia quadrangula (Clusiaceae) - Martínez-Mendoza, Beatriz Itzel; Juárez-Trujillo, Naida; Mendoza-López, María Remedios; Monribot-Villanueva, Juan Luis; Guerrero-Analco, José Antonio; Jiménez Fernández, Maribel (Instituto de Ecología, A.C., 2023)
Background and Aims: The Clusiaceae family is known for its bioactive compounds with beneficial antioxidant and anti-inflammatory properties. The objectives of this study were to 1) identify and quantify the individual polyphenol compounds in the methanolic extract from peel, pulp and aril of the fruit of Clusia quadrangula by UPLC-MSMS, evaluate their antioxidant properties, 2) analyze the fatty acid profile, minerals composition and 3) determine the antibacterial activity against pathogenic bacteria of the methanolic extract.Methods: Physicochemical properties, antioxidants and bioactive compounds, fatty acid profile and mineral content were analyzed using a Microplate Spectrophotometer, Ultra High Performance Liquid Chromatography coupled with a triple quadrupole Mass Spectrometer, Gas Chromatography coupled with a Mass Spectrometer and Microwave Plasma Atomic Emission Spectroscopy.Key results: Twenty phenolic compounds were identified and quantified plus the precursor shikimic acid (103.55 µg/g solids). Procyanidin B2 (41.56 µg/g solids), (−)-epicatechin (34.07 µg/g solids), and ellagic acid (27.58 µg/g solids) were found in greater quantity in the methanolic extract of the pulp. Palmitic and linoleic acid were the most abundant fatty acids in the pulp, peel, and aril, and linolenic acid was present in the pulp. The pulp also exhibited the highest amount of total polyphenolic compounds (24.33 mg GAE/g) and reducing power evaluated by FRAP (18.697 mg ET/g). Analysis of the minerals revealed that all fractions are rich in magnesium, potassium, sodium, and calcium. The results showed that the methanolic extract of the different parts of the fruit had antibacterial properties against Salmonella typhi, Escherichia coli, Staphylococcus aureus, and Enterococcus faecalis. Conclusions: These results indicate that different parts of the C. quadrangula fruit are a rich source of natural antioxidants and possess antibacterial properties. Therefore, it can be considered for use as ingredient or additive in the cosmetic, pharmaceutical, or food industries.